IDENTIFICATION OF RESISTANT SOURCES TO WHIP SMUT OF SUGARCANE CAUSED BY SPORISORIUM SCITAMINEUM - J , SAILAJA RANI (The Journal of Research ANGRAU, 2026)
Whip smut causing pathogen in Sugarcane has the potential to cause substantial lossesto farmers. Sugarcane cultivars which are susceptible, should be replaced with resistant onesthat have desirable yield attributes. Twenty four Sugarcane genotypes were selected for artificialinoculation to identify resistant genotype to smut disease. Setts dipped in smut spore suspensionbefore planting and collected data on production of smutted whips in genotypes. Among thegenotypes tested, 2016 V130 was found resistant, while 2016 V 35, 2017 V 16, 2018 V 42, 2018 V48, 2018 V 53 and 2018 V 79 were found moderately resistant to smut pathogen.